Evaluation of elite rice lines for resistance to Kenya blast fungus (Magnapothe Oryzae) - Juma, Roselyne U.; Murori, Rosemary; Felister N, Mbute; Miano, Douglas W.; Cobb, Joshua N. (Peertechz Publications Private Limited, 2024)
Blast resistance tends to often break down, these necessitate search-resistant genes. The screen house experiment was conducted in 2019 and 2020. A total of 56 rice genotypes, (Elite lines, monogenic lines, and local), were screened against ten Kenya isolates of Mangnaporthe oryzae. The establishment was by direct seeding of previously sprouted seeds. A completely Randomized Design (CRD) with two replicates was adopted. Inoculation was done 21 days after planting. Plants were maintained in the moist chamber (26–28 0C) for 48 hrs, then moved into an incubation chamber (25 ◦C ± 2). Disease assessment commenced 48 hours after inoculation until 21 days to full infection. Disease evaluations were performed according to the Standard Evaluation System of IRRI. Polymerase Chain Reactions (PCR) were carried out, blast resistant loci were identified using varied genetic markers that co-segregate with specific resistant loci Analysis was implemented in R version 3.3.2 (R Core Team, 2016). BLUPs were computed, in a mixed model to estimate the random effect of the genotypes. The data was subjected to analysis of variance and means separated by Tukey’s test at P < 0.05. Cluster analyses were performed in JMP software version 11.2 for Windows. Seven genotypes (IR12A311, IR10M210, IR74, 1R02A127, IR09A130, R66 and IR10N230) were more susceptible, IR13N152 and IR14F711 were more resistant to all Isolates. The monogenic lines IRBLsh-B and IRBLkh-K3 which carry blast-resistant genes, were susceptible to at least seven Kenya isolates. The local checks (Basmati 370, BAS 270 (pi9), BW196, and BAS370 (pi9) were highly susceptible. The genotype IR12F711 was consistently resistant to all Kenya Isolates.